Pengaruh Model Pembelajaran RANDAI Terhadap Keterampilan Pemecahan Masalah Peserta Didik Kelas X IPA SMAN 1 Matur - Laras Trimayora; Fitri Arsih; Heffi Alberida; Yosi Laila Rahmi (STKIP ROKANIA, 2022)
The low problem solving skills of students is caused by the ongoing learning process that is not yet fully centered on students and the learning model used is not optimal and varied. This study aims to determine the problem solving skills of students in class X IPA SMAN 1 Matur. This type of research is a quasi-experimental study with a pretest-posttest control group design. The population in this study were all students of class X science at SMAN 1 Matur in the academic year 2021/2022. The research sample was students of class X IPA 1 as the control class and X IPA 2 as the experimental class. Sampling using total sampling technique. The instrument used is a question sheet in the form of an essay question consisting of 6 questions. The results showed that the problem-solving skills of the experimental class were higher than that of the control class with an average pretest of the experimental class (66.71), the posttest of the experimental class (77.84), the pretest of the control class (59.13) and the posttest of the control class ( 68.55). Data analysis was carried out by using paired sample t-test which showed that the significant value of the sample class was <0.05, namely 0.00. So it can be concluded that there is an effect of applying the RANDAI learning model to the problem solving skills of students in class X IPA SMAN 1 Matur.